Interaction Pathways and Structure-Chemical Transformations of Alginate Gels in Physiological Environments - Urbanova, Martina; Pavelkova, Miroslava; Czernek, Jiri; Kubova, Katerina; Vyslouzil, Jakub; Pechova, Alena; Molinkova, Dobromila; Vyslouzil, Jan; Vetchy, David; Brus, Jiri (Biomacromolecules, 2019)
The remarkably diverse affinity of alginate (ALG) macromolecules for polyvalent metal ions makes cross-linked alginate gels an outstanding biomaterial. Surprisingly, however, very little is known about their interactions and structural transformations in physiological environments. To bridge this gap, we prepared a set of ALG gels cross-linked by various ions and monitored their structural changes at different media simulating gastric and intestinal fluids and cellular environments. For these studies, we used multinuclear solid-state NMR (ss-NMR) spectroscopy, which revealed a range of competitive ion-exchange and interconversion reactions, the rate of which strongly depended on the nature of the cross-linking metal ions. Depending on the environment, ALG chains adopted different forms, such as acidic (hydro)gels stabilized by strong hydrogen bonds, and/or weakly cross-linked Na/H-gels. Simultaneously, the exchanged polyvalent ions extensively interacted with the environment even forming in some cases insoluble phosphate microdomains directly deposited in the ALG bead matrix. The extent of the transformations and incorporation of secondary phases into the alginate beads followed the size and electronegativity of the cross-linking ions. Overall, the applied combination of various macroscopic and biological tests with multinuclear ss-NMR revealed a complex pathway of alginate beads transformations in physiological environments.
Keywords: Metals; vodíková vazba; buněčné mikroprostředí; Biocompatible Materials; algináty; Cross-Linking Reagents; biokompatibilní materiály; gely; Gels; kovy; Cellular Microenvironment; Humans; Alginates; Hydrogen Bonding; reagencia zkříženě vázaná; Magnetic Resonance Spectroscopy; lidé; magnetická rezonanční spektroskopie